Transient increase in glucose variability during Ramadan fasting in patients with insulin-treated type 2 diabetes: A preliminary study. Issue 4 (April 2023) - Elmalti, Akrem; Mukhtar, Mamoun; Kenz, Sami; Skaria, Sijomol; Elgzyri, Targ
Abstract: Aim: We aimed to examine the effect of Ramadan fasting on interstitial glucose control and variability before, during, and after Ramadan in type 2 diabetes patients receiving insulin therapy. Methods: Participants received a flash glucose monitoring (FGM) system one week before Ramadan that was removed on the sixth or seventh day (pre- and early Ramadan periods) of Ramadan and a second FGM system one week before the end of Ramadan that was removed one week after the end of Ramadan (late and post-Ramadan periods). Fasting blood samples were collected during the pre-, early, and late Ramadan study visits and tested for HbA1c, serum creatinine, and plasma glucose levels. Results: Thirty-four patients were prospectively included. The standard deviation and coefficient of variation of glucose concentrations were higher in the early Ramadan period than in the pre-Ramadan period, but did not differ in the late or post-Ramadan periods. Changes in the early Ramadan period were restricted to males and patients aged <55 years. No significant changes were observed in the average glucose level, glucose management indicator, time in range, time in hyperglycemia, or time in hypoglycemia at any time point. Conclusions: Ramadan fasting in patients with insulin-treated type 2 diabetes is associated with an initial increase in glucose variability that quickly returned to pre-Ramadan levels. Ramadan fasting was not associated with any significant changes in glycemic control measures. Highlights: The effect of Ramadan fasting on glucose control and variability in insulin-treated type 2 diabetes patients was examined. Ramadan fasting caused an initial increase in glucose variability that quickly returned to pre-Ramadan levels. Men and younger patients are at higher risk for this initial increased glucose variability. Ramadan fasting did not cause significant changes in glycemic control measures in these patients.